2014
DOI: 10.1159/000366406
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Features of Renal Carcinoma Associated with Xp11.2 Translocations/TFE3 Gene Fusions: A Case Report with Voided and Catheterized Urine Cytology and a Literature Review

Abstract: Background: Renal carcinomas associated with Xp11.2 translocations/TFE3 gene fusions are rare subtypes of renal neoplasm that predominantly occur in younger individuals. There are very few reports describing the cytologic features of these tumors. Case: A 27-year-old man presented with hematuria and was found to have a mass in the lower part of the right kidney. Cytology of catheterized urine obtained from the right renal pelvis showed clusters of cells with abundant clear or eosinophilic granular cytoplasm, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Ancillary studies performed on CNBs and cell blocks of FNA and urine specimens revealed that the tumors were negative or focally positive for pancytokeratin, negative for EMA, but consistently positive for CD10, indicating that these stains are very useful screening tests for translocation carcinomas. CAIX evaluation, which was performed in only one tumor, was negative . In contrast, AMACR was positive in all tumors tested and although, by itself, may have raised the possibility of a PRCC, coupled with negativity or very focal positivity for CK7, was unusual.…”
Section: Rcc Subtypes Recognized In End‐stage Kidney Diseasementioning
confidence: 84%
See 2 more Smart Citations
“…Ancillary studies performed on CNBs and cell blocks of FNA and urine specimens revealed that the tumors were negative or focally positive for pancytokeratin, negative for EMA, but consistently positive for CD10, indicating that these stains are very useful screening tests for translocation carcinomas. CAIX evaluation, which was performed in only one tumor, was negative . In contrast, AMACR was positive in all tumors tested and although, by itself, may have raised the possibility of a PRCC, coupled with negativity or very focal positivity for CK7, was unusual.…”
Section: Rcc Subtypes Recognized In End‐stage Kidney Diseasementioning
confidence: 84%
“…Several reports have been published describing the cytologic findings of MiT translocation RCC, and all are instances of Xp11 translocation RCC. They included evaluations of touch imprints of image‐guided CNBs of renal masses; FNAs of a renal mass, lung, and mediastinal metastases; and urine cytology . The patients were ages 1 to 58 years and had an equal distribution according to sex.…”
Section: Rcc Subtypes Recognized In End‐stage Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge there are only five case reports that describe the cytologic features of this group of RCC (Table ). Two of them were fine‐needle aspirations, one was urine cytology, and two others were touch imprint of resected or biopsies specimens . Although the cytologic features are overlapping with papillary RCC and clear cell carcinoma, presence of psammoma bodies and hyaline globules/nodules should alert the cytopathologists to the possibility of MiTF family translocation RCC thereby prompting them to initiate ancillary studies.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Given the paucity of the cytologic findings in the literature, we describe the fine-needle aspiration (FNA) findings including a review of literature. [5][6][7][8][9][10] Given the paucity of the cytologic findings in the literature, we describe the fine-needle aspiration (FNA) findings including a review of literature.…”
mentioning
confidence: 99%